STUDENT SATISFACTION WITH THE IMPLEMENTATION OF E-LEARNING MANAGEMENT EFFORTS TO IMPROVE THE QUALITY OF HIGHER EDUCATION TRANSPARENCY - Arsal, Muryani; Fitri, Fitri (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
E-learning refers to the transformation of knowledge through a network on a computer or other electronic device. This study aims to determine the perception of accounting student satisfaction with e-learning accounting courses before and during Covid-19 at the Muhammadiyah University of Makassar, Indonesia. Data was collected from a sample of 328 students enrolled accounting courses. The research employs a quantitative design, with data was collected through google form. Data were analysis using SPSS to determine student demographics, data normality and to investigate differences in students satisfaction with accounting e-learning before and during the covid. The findings reveal differences in accounting students satisfaction of before and during covid-19 towards accounting e-learning. The study also, indicated that students' perceptions of e-learning are influenced by students' knowledge of technology and the availability of internet access and the high cost of data.